Pemberian Edukasi Nutrisi Balita - Syaputri Syaputri; Nur Aini Mahmudah; Nabila Febri Dea; Putri Larasati; Panca Rizky Kharisma; Roni Riski Dinata; Ar-Rahman Tanjung; Maria Paulina Irma Susanti; Dwi Novitasari (Yayasan Inspirasi El Burhani, 2023)
Introduction: Stunting is a prevalent problem in early childhood development, characterized by impaired growth and height at an age below the standard threshold. Addressing stunting in the first 1000 days of life is critical to preventing long-term consequences for physical and cognitive development. Objective: The aim of this community service was to improve the awareness and health of the Sokaraja. This study aims to explore and evaluate the impact of nutrition interventions on stunted children under five. Methods: The method implemented to overcome the problem of stunting in children is by conducting direct counseling on Saturday, July 8, 2023, from 9:00 a.m. to 5:00 p.m. The target audience is mothers at Posyandu Harapan 3, Sokaraja, with 30 participants. Then, using lecture and discussion methods with media and PowerPoint slides about toddler nutrition and leaflets about the importance of toddler nutrition, demonstrate cooking foods that contain nutrients and protein. The counseling process was conducted personally for about an hour. Results: The results are three age categories of children who have different heights and weights. First, children aged 0–1 years have an average height of 68.8 cm and an average weight of 9.5 kg. Second, children aged 2–3 years have an average height of 84.7 cm and an average weight of 11.5 kg. Third, children aged 3-5 years have an average height of 96.1 cm and an average weight of 15.7 kg. Conclusion: Nutrition counseling activities are well organized. There is an increase in mothers' knowledge about toddler nutrition and stunting.